2017
DOI: 10.1016/j.amepre.2017.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Physical Activity: Moderation of Individual Factors by Neighborhood Environment

Abstract: Introduction Less than a third of U.S. adolescents meet federal physical activity (PA) guidelines. Understanding correlates of PA at multiple levels of the Social Ecological Model could improve PA interventions among youth. This study examines: (1) associations between factors across the Social Ecological Model including psychosocial factors, perceived neighborhood physical and social environment characteristics, and adolescent moderate/vigorous PA (MVPA); and (2) whether perceived neighborhood characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 32 publications
7
25
0
Order By: Relevance
“…One study found that among adolescents living in activity-supportive neighborhoods (e.g., high access to activity resources), there were stronger positive associations between psychosocial factors and physical activity. 19 In contrast, living in a less walkable neighborhood may contribute to male adolescents’ perceived barriers and motivate them to seek physical activity opportunities outside their neighborhood. Males with high decisional balance living in high walkable neighborhoods may also be from high SES households and have parents that model or encourage physical activity and sports beyond the neighborhood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study found that among adolescents living in activity-supportive neighborhoods (e.g., high access to activity resources), there were stronger positive associations between psychosocial factors and physical activity. 19 In contrast, living in a less walkable neighborhood may contribute to male adolescents’ perceived barriers and motivate them to seek physical activity opportunities outside their neighborhood. Males with high decisional balance living in high walkable neighborhoods may also be from high SES households and have parents that model or encourage physical activity and sports beyond the neighborhood.…”
Section: Discussionmentioning
confidence: 99%
“…1719 One study found interactions between several psychosocial factors (e.g., social support and friend norms) and physical activity resource availability in relation to adolescent MVPA, with stronger positive associations found among those in neighborhoods with high vs. low resource availability. 19 However, an important limitation of previous research is the assumption that most of adolescents’ physical activity occurs in the neighborhood. No study that we are aware of has examined environment-psychosocial interactions in relation to context-specific physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…In free time, personal choice becomes a stronger factor and strategies enabling access to equipment and areas that allow unstructured physical activity can help children and adolescents be more active 44,45 . This may be particularly important for children living in low‐income areas, for whom free time PA represents about half of total PA.…”
Section: Discussionmentioning
confidence: 99%
“…For example, an examination of the literature on diet and physical activity barriers highlights a framework whereby a supportive physical environment fosters higher levels of interpersonal and individual-level support and in turn healthier behaviours (Caspi, Sorensen, Subramanian, & Kawachi, 2012;D'Angelo, Fowler, Nebeling, & Oh, 2017;Dean & Sharkey, 2011;Dwyer, Patel, Nebeling, & Oh, 2018). …”
mentioning
confidence: 99%